Jejunal Extragonadal Germ Cell Tumor Presenting as an Abdominal Mass: A Case Report - Asutkar, Kartik G.; Saldanha, Smitha C.; Maleyur, Vivek B.; Babu, M.C. Suresh; Lokesh, K.N.; Rudresh, A.H.; Rajeev, L.K. (Indian Journal of Medical and Paediatric Oncology, 2025)
Extragonadal germ cell tumors (EGGCTs) are rare malignancies that arise outside the gonads and occur infrequently in the gastrointestinal tract. Their presentation often mimics that of other abdominal neoplasms, posing diagnostic challenges. Histopathological and immunohistochemical confirmation, along with tumor marker evaluation, is essential for diagnosis. Early diagnosis and platinum-based chemotherapy can significantly improve patient outcomes. A 25-year-old male presented with abdominal pain, a palpable mass in the umbilical region, and subacute intestinal obstruction. Imaging revealed a heterogeneously enhancing lesion in the mesentery and a subcapsular lesion in the left kidney. Emergency debulking surgery was then performed. Histopathology and immunohistochemistry confirmed an EGGCT favoring a yolk sac tumor. Serum marker levels were elevated with AFP (alpha-fetoprotein) of 854 IU/mL, 23 mIU/mL of β-human chorionic gonadotrophin (β-hCG); 277 U/L of LDH. Ultrasonography of the testes revealed microcalcifications in the left testis, without overt malignancy. The patient was diagnosed with a Stage IIIC extragonadal non-seminomatous germ cell tumor. He was started on an EP regimen owing to poor pulmonary function, followed by BEP, and was scheduled for a high inguinal orchidectomy. This case highlights the importance of including EGGCTs in the differential diagnosis of abdominal masses in young males. A multidisciplinary approach with timely histological and oncological assessments is vital. Early intervention with platinum-based chemotherapy offers a favorable prognosis, even in advanced stages. Given the rarity of this presentation, further studies are needed to refine diagnostic and therapeutic strategies.
Keywords: extragonadal germ cell tumor; yolk sac tumor; abdominal mass; non-seminomatous germ cell tumor; young adult